Uji Aktivitas Sitotoksik dan Analisis Fitokimia Ekstrak Etanol Daun Sampare (Glochidion sp.) - Ganis Oktalia; Linus Y. Chrystomo; Aditya K. Karim (Jurusan Biologi FMIPA Universitas Cenderawasih, 2017)
Sampare (Glochidion sp., Family: Phyllantaceae) is a plant which grows dominant in Biak, Papua. Based on the local wisdom of the community, by hereditary, it can be used as an herbal medicine to treat the malaria disease. This study aims to determine the toxicity of LC50 and to know the phytochemical compounds of extracted leaf of Glochidion sp using ethanol. The Brine Shrimp Lethality Test (BSLT) and phytochemical screening using reagent chemical substance methods were used in this research. The results of this study can be concluded that the toxicity of extracted leaf of Glochidion sp. using ethanol was low, with LC50 = 758.58 ppm and the results of phytochemical analysis showed the existence of the content of alkaloids, flavonoids, saponins, tannins and quinones. But, the steroids and triterpenoids could not be found in the extracted leaf of Glochidion sp using ethanol. Therefore, for further research is needed to isolate the bioactive compounds and in vivo test on the plasmodium, which cause the malaria disease. Key words: Glochidion sp., malaria desease, Brine Shrimp Lethality Test (BSLT), LC50, phytochemical analysis